CASES OF SELF-MANAGEMENT IN BRAZIL: A META-SYNTHESIS - Penteado, Raphael Camargo; Benini, Elcio Gustavo; Nascimento, Daniel Teotonio do; Petean, Gustavo Henrique; Nemirovsky, Gabriel Gualhanone [UNESP] (Editorial Cuadernos Sofia, 2020)
This study aimed to present a theoretical essay about the attempts of self-managed organization in Brazil. Therefore, a literature search was conducted of previous studies using the meta-synthesis methodology, as proposed by Hoon (2013). In the research design, the procedures for performing the meta-synthesis were detailed, in which 76 articles were retrieved and 11 used for the preparation of the cross-sectional analysis and synthesis, resulting in a theoretical advance beyond what was proposed individually in the case studies used. It was found that such ventures are not truly self-managed organizations, but rather come close to this mode of organization, and promote alternatives for work, income and the possibility of social well-being, as well as seeking to structure themselves collectively, voluntarily and in solidarity. Due to these characteristics of these projects, government support is possible in the form of credit lines and development programs. In addition, the study demonstrates that university participation, through incubators, is fundamental to an educational process geared to collectivism and more participatory forms of management. Therefore, the present study concludes that the joint performance of the public authorities and the university in these productive organizations are essential for these to be constituted and developed.
Keywords: Self-management; Cooperatives; Solidarity Economy; Case Study; Organization